BIMBINGAN KONSELING BEHAVIORAL LEMBAGA UBUDIYAH DALAM MENGAKTIFKAN PELAKSANAAN SHOLAT BERJAMA’AH SANTRI DI PONDOK PESANTREN DARUSSALAM PUTRI UTARA MASA ABDI 2021/2022 - Masnida, Masnida; Ariati, Devi (JKaKa:Jurnal Komunikasi dan Konseling Islam, 2023)
The behavior approach itself is one approach in guidance and counseling to overcome maladaptive behavior towards adaptive behavior. The focus of research in writing this thesis is Behavioral Counseling carried out by the Ubudiyah Institute in activating the implementation of congregational prayers for students at the Darussalam Putri Utara Islamic Boarding School. The purpose of this paper is to carry out several methods, namely the method of advice, the method of punishment, the method of attention, the method of supervision and the method of exemplary, so that the students can pray in congregation more actively. In this research, the type of research used is qualitative research. Data collection methods used are observation, interviews, and documentation. The results of the study show that the behavioral approach can increase the activation of the congregational prayer discipline of Darussalam Islamic boarding school students by using several methods, namely the exemplary method, the method of punishment, the method of advice, the method of habituation, and the method of experience.